2018
DOI: 10.1161/jaha.117.007165
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Safety, Long‐Term Noncardiovascular Safety, and Efficacy of Sodium–Glucose Cotransporter 2 Inhibitors in Patients With Type 2 Diabetes Mellitus: A Systemic Review and Meta‐Analysis With Trial Sequential Analysis

Abstract: BackgroundThe cardiovascular and long‐term noncardiovascular safety and efficacy of SGLT2 (sodium–glucose cotransporter 2) inhibitors have not been well documented.Methods and ResultsFor cardiovascular outcomes, we performed a meta‐analysis with trial sequential analysis of randomized controlled trials and adjusted observational studies, each with a minimum of 26 weeks and 2000 patient‐years of follow‐up. For long‐term noncardiovascular safety and efficacy outcome analyses, we included only randomized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 59 publications
5
71
0
8
Order By: Relevance
“…Core outcome sets were defined in the protocol of the RCTs, which aimed to reduce selective reporting biases, but in many cases the unavailability of data was in safety (adverse events) outcomes. Despite sparse data for some outcomes, all models appeared to converge from visual analysis of history and trace plots, and the estimates from pairwise analyses and network meta-analyses in the present study were similar to those from meta-analyses conducted previously [10][11][12][13]41]. Furthermore, it was not possible to assess individual treatments in the network but only combined in treatment groups; however, by comparing the class effects of treatments, rather than individual treatment effects, statistical power was increased.…”
Section: Discussionsupporting
confidence: 83%
“…Core outcome sets were defined in the protocol of the RCTs, which aimed to reduce selective reporting biases, but in many cases the unavailability of data was in safety (adverse events) outcomes. Despite sparse data for some outcomes, all models appeared to converge from visual analysis of history and trace plots, and the estimates from pairwise analyses and network meta-analyses in the present study were similar to those from meta-analyses conducted previously [10][11][12][13]41]. Furthermore, it was not possible to assess individual treatments in the network but only combined in treatment groups; however, by comparing the class effects of treatments, rather than individual treatment effects, statistical power was increased.…”
Section: Discussionsupporting
confidence: 83%
“…Empagliflozin was significantly associated with a lower risk of composite renal events (OR 0.72, 95% CI 0.60‐0.86), an effect which was largely driven by the EMPA‐REG study . Finally, a meta‐analysis of five trials comprising 13 510 patients revealed lower rates of AKI with SGLT2‐i versus controls (OR 0.80, 95% CI 0.67‐0.96) …”
Section: Discussionmentioning
confidence: 89%
“…8 Finally, a meta-analysis of five trials comprising 13 510 patients revealed lower rates of AKI with SGLT2-i versus controls (OR 0.80, 95% CI 0.67-0.96). 9 An observational study which included users of SGLT2-i versus non-users in two large cohorts did not find an increased risk of AKI in the inpatient setting with SGLT2-i. 10 Conversely, analysis of the cases reported to the FDA showed an increased risk of AKI with SGLT2-i versus other glucose-lowering agents; however, this database is limited by reporting bias.…”
Section: Discussionmentioning
confidence: 92%
“…In our opinion, pharmacological therapy should be applied to support lifestyle intervention and should aim to facilitate increasing insulin sensitivity. As important options, glucagon‐like peptide‐1 (GLP‐1) analogues and sodium‐glucose co‐transporter‐2 (SGLT‐2) inhibitors could be valuable, as they lower HbA1c along with a decrease in body weight and in long‐term cardiovascular risk without increased risk of hypoglycaemia 14, 15…”
Section: Discussionmentioning
confidence: 99%